Prognostic Models of Mortality Following First‐Ever Acute Ischemic Stroke: A Population‐Based Retrospective Cohort Study - Mustapha Mohammed (5737328) (2025)
Background and Aims There is a lack of population‐based studies focusing on guideline‐based prognostic models for stroke. This study aimed to develop and validate a prognostic model that predicts mortality following a first‐ever acute ischemic stroke. Methods The study included 899 adult patients ( ≥ 18 years) with confirmed diagnosis of first‐ever acute ischemic stroke enrolled in the Malaysian National Stroke Registry (NSR) from January 2009 to December 2019. The primary outcome was mortality within 90 days post‐stroke (266 events [29.6%]). The prognostic model was developed using logistic regression (75%, n= 674) and internally validated (25%, n= 225). Model performance was assessed using discrimination (area under the curve (AUC]) and calibration (Hosmer‐Lemeshow test [HL]). Results The final model includes factors associated with increased risk of mortality, such as age (adjusted odds ratio, aOR 1.06 [95% confidence interval, CI 1.03, 1.10; p < 0.001]), National Institutes of Health Stroke Scale (NIHSS) score aOR 1.08 (95% CI 1.08, 1.13; p = 0.004), and diabetes aOR 2.29 (95% CI 1.20, 4.37; p = 0.012). The protective factors were antiplatelet within 48 h. aOR 0.40 (95% CI 0.19, 0.81; p = 0.01), dysphagia screening aOR 0.30 (95% CI 0.15, 0.61; p = 0.001), antiplatelets upon discharge aOR 0.17 (95% CI 0.08, 0.35; p < 0.001), lipid‐lowering therapy aOR 0.37 (95% CI 0.17, 0.82; p = 0.01), stroke education aOR 0.02 (95% CI 0.01, 0.05; p < 0.001) and rehabilitation aOR 0.08 (95% CI 0.04, 0.16; p < 0.001). The model demonstrated excellent performance (discrimination [AUC = 0.94] and calibration [HL, X2 p = 0.63]). Conclusion The study developed a validated prognostic model that excellently predicts mortality after a first‐ever acute ischemic stroke with potential clinical utility in acute stroke care decision‐making. The predictors could be valuable for creating risk calculators and aiding healthcare providers and patients in making well‐informed clinical decisions during the stroke care process. Other Information Published in: Health Science Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/hsr2.70445